Correction: Engineering surface state density of monolayer CVD grown 2D MoS2 for enhanced photodetector performance. - Gowtham Polumati; Chandra Sekhar Reddy Kolli; Andres de Luna Bugallo; Parikshit Sahatiya (PLoS ONE, 2024)
[This corrects the article DOI: 10.1371/journal.pone.0297825.].